1989
DOI: 10.1016/0014-5793(89)80654-4
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and antigenic characterization of CD45 polypeptides expressed on plasma membrane and internal granules of human neutrophils

Abstract: The expression of CD45 polypeptides, a phosphotyrosine phosphatase complex specific of leukocytes, has been investigated in both resting and activated neutrophils by using anti-CD45 monoelonal antibodies (MAb) which specifically recognize different polypeptide components of the CIM5 molecular complex. Polypeptides of 180 and 130-150 kDa were equally precipitated by either a conventional CD45 MAb recognizing an antigenic determinant shared by the four CD45 glycoproteins (220, 205, 190 and 180 kDa) or by the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 35 publications
3
14
0
Order By: Relevance
“…A member of the transmembrane class of tyrosine phosphatases, CD45 has been found on secretory granules and the plasma membranes of neutrophils (23). Stimulation with a variety of agents has been shown to enhance the expression of CD45 on the plasma membrane (24), a phenomenon thought to contribute to the desensitization of neutrophils following further stimulation with fMLP (25).…”
Section: Polymorphonuclear (Pmn)mentioning
confidence: 99%
“…A member of the transmembrane class of tyrosine phosphatases, CD45 has been found on secretory granules and the plasma membranes of neutrophils (23). Stimulation with a variety of agents has been shown to enhance the expression of CD45 on the plasma membrane (24), a phenomenon thought to contribute to the desensitization of neutrophils following further stimulation with fMLP (25).…”
Section: Polymorphonuclear (Pmn)mentioning
confidence: 99%
“…This recovery could be due either to the release of immature neutrophils from bone marrow or to recirculation of neutrophiis expressing lower CD45 ieveis from lung capillaries [25]. We have previously demonstrated that CD45 molecules arc stored in resting neutrophils on membranes from the readily translocatabie tertiary secretory granuies, as weli as in that from specific granules [9], and it is known that intraceilular compartmcntaiization of these organelles is regulated during neutrophil activation [26].…”
Section: Discussionmentioning
confidence: 99%
“…Spain. branes [9]. However, the biochemical relation between these 180-and I30-l50-kD polypeptides was not established in such studies.…”
Section: Introductionmentioning
confidence: 98%
“…With respect to phosphatases, a membrane-associated phosphotyrosine phosphatase activity has been observed in human neutrophils [5]. CD45, a phosphotyrosine phosphatase, is mobilized from specific and/or tertiary granules to the plasma-membrane fraction when neutrophils are stimulated by fMet-Leu-Phe or CB [35]. In vitro, the specific activities of phosphotyrosine phosphatases are much higher than those of tyrosine kinases [36].…”
Section: Discussionmentioning
confidence: 99%
“…5 and Table 1). This may be due to that CB pretreatment inducing mobilization of CD45 from granules to the membrane fraction [35] and thus increasing the phosphatase activity in the membrane. This hypothesis should be tested.…”
Section: Discussionmentioning
confidence: 99%